Ancient Transcription Factors in the News - Irina Artsimovitch (American Society for Microbiology, 2019)
ABSTRACT In every cell from bacteria to mammals, NusG-like proteins bind transcribing RNA polymerase to modulate the rate of nascent RNA synthesis and to coordinate it with numerous cotranscriptional processes that ultimately determine the transcript fate. Housekeeping NusG factors regulate expression of the bulk of the genome, whereas their highly specialized paralogs control just a few targets. In Escherichia coli, NusG stimulates silencing of horizontally acquired genes, while its paralog RfaH counters NusG action by activating a subset of these genes. Acting alone or as part of regulatory complexes, NusG factors can promote uninterrupted RNA synthesis, bring about transcription pausing or premature termination, modulate RNA processing, and facilitate translation. Recent structural and mechanistic studies of NusG homologs from all domains of life reveal molecular details of multifaceted interactions that underpin their unexpectedly diverse regulatory roles. NusG proteins share conserved binding sites on RNA polymerase and many effects on the transcription elongation complex but differ in their mechanisms of recruitment, interactions with nucleic acids and secondary partners, and regulatory outcomes. Strikingly, some can alternate between autoinhibited and activated states that possess dramatically different secondary structures to achieve exquisite target specificity.